The impact of (E/Z)-isomerization and aggregation on the color of rhodoxanthin formulations for food and beverages. (1st December 2020) - Schex, Roland; Bonrath, Werner; Schäfer, Christian; Schweiggert, Ralf
Highlights: An outstanding range of red, pink, and purple color hues was achieved with rhodoxanthin. ( E/Z )-isomerization reactions of rhodoxanthin modulated its color in acetone. Aggregation of rhodoxanthin was impacted by steering its ( E/Z )-isomeric ratio. Solvent-based emulsification and wet-milling enabled obtaining red and purple color hues in water. Abstract: Rhodoxanthin is a scarcely explored carotenoid with an extraordinarily large chromophore and high potential to function as red pigment. We report broad ranges of color shades accessible with rhodoxanthin across an unprecedented wide range of ( E/Z )-ratios by thermal ( E/Z )-isomerization, lyotropic aggregation, and two different formulation techniques, covering shares of the (all- E )-configured isomer of 19–91%. At ( E/Z )-ratios of 75 and 23%, rhodoxanthin ( E/Z )-isomer mixtures in acetone revealed color hues (CIE-h°) ranging from 20–44° to 36–54°. Lyotropic aggregation of rhodoxanthin ( E/Z )-isomer mixtures in acetone/water yielded red (CIE-h° = 29°) to purple (−7°) and red-orange (44°) to pink (9°) color hues at (all- E )-proportions of 73 and 20%, respectively. Red and purple color hues were produced by micronization using solvent-based emulsification (CIE-h° = 33–37°) and high-performance wet-milling (−6°). The presented technological strategies for formulating nature-identical rhodoxanthin into water-dispersible forms showed its potential as promising pigment for imparting red, pink, and purple color to foods and beverages.